A STUDY TO ASSESS JOB STRESS AND ITS IMPACT ON QUALITY OF LIFE: A DESCRIPTIVE CROSS-SECTIONAL STUDY - KAUSAR , F; DITTA , UA; HASHMI , M; JABEEN , S; NAWAZ , B (Biological and Clinical Sciences Research Journal, 2024)
Job stress is a significant occupational hazard among nurses, adversely affecting their health, well-being, and professional performance. In Pakistan, where nurses face high workloads and limited institutional support, stress levels are particularly concerning. This study aimed to assess job stress and its impact on the quality of life among nurses working in tertiary care hospitals in Lahore. Methods: A descriptive cross-sectional study was conducted among 169 nurses from Sheikh Zayed Hospital and Services Hospital, Lahore. Data were collected using a structured questionnaire, including the Expanded Nursing Stress Scale (ENSS) and SF-12 Likert scale. Descriptive and inferential statistics were used to analyze the data. Results: The findings revealed that 40% of nurses experienced mild stress, 13% reported moderate stress, and 6.7% suffered from severe stress. Stress significantly impacted the quality of life, with limitations in daily activities, emotional problems, and social relationships. Younger nurses and unmarried individuals reported higher stress levels. Significant associations were observed between stress levels and demographic variables such as gender, age, and marital status (p < 0.05). Conclusion: Job stress among nurses in tertiary care hospitals significantly affects their quality of life, emphasizing the need for targeted interventions, including stress management programs and institutional reforms. Improving the work environment and supporting nurses can enhance their well-being and professional performance.